2022
DOI: 10.2147/jir.s379331
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Mechanisms are Activated in Circulating Lymphocytes of Hospitalized Covid-19 Patients

Abstract: Purpose Reactive oxygen species (ROS) are an important part of the inflammatory response during infection but can also promote DNA damage. Due to the sustained inflammation in severe Covid-19, we hypothesized that hospitalized Covid-19 patients would be characterized by increased levels of oxidative DNA damage and dysregulation of the DNA repair machinery. Patients and Methods Levels of the oxidative DNA lesion 8-oxoG and levels of base excision repair (BER) proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Increased levels of oxidized guanine were generally observed in COVID-19 patients with much higher levels in those with more severe disease. In a second study, perhaps surprisingly, similar levels of 8-oxo-G were observed in peripheral blood mononuclear cells (PBMCs) from healthy and SARS-CoV-2-infected individuals [172]. However, elevated levels of some, but not all, base excision repair proteins (for example, POLD1, MPG, ligase 1 and FEN1) and double-strand break repair proteins (for example, Chk1, RAD50 and RAD51) were reported in COVID-19 patients [172].…”
Section: Sars-cov-2 and Ddrmentioning
confidence: 90%
See 1 more Smart Citation
“…Increased levels of oxidized guanine were generally observed in COVID-19 patients with much higher levels in those with more severe disease. In a second study, perhaps surprisingly, similar levels of 8-oxo-G were observed in peripheral blood mononuclear cells (PBMCs) from healthy and SARS-CoV-2-infected individuals [172]. However, elevated levels of some, but not all, base excision repair proteins (for example, POLD1, MPG, ligase 1 and FEN1) and double-strand break repair proteins (for example, Chk1, RAD50 and RAD51) were reported in COVID-19 patients [172].…”
Section: Sars-cov-2 and Ddrmentioning
confidence: 90%
“…In a second study, perhaps surprisingly, similar levels of 8-oxo-G were observed in peripheral blood mononuclear cells (PBMCs) from healthy and SARS-CoV-2-infected individuals [172]. However, elevated levels of some, but not all, base excision repair proteins (for example, POLD1, MPG, ligase 1 and FEN1) and double-strand break repair proteins (for example, Chk1, RAD50 and RAD51) were reported in COVID-19 patients [172]. In addition, it was noted that more highly regulated DDR pathway protein expression was correlated with severity of disease.…”
Section: Sars-cov-2 and Ddrmentioning
confidence: 90%